Evaluación de la gestión del suministro de medicamentos antirretrovirales en una institución prestadora de salud Medellín-Colombia 2013 (2016)
ABSTRACT: There is the need to promote rational drug supply, according to the patient’s need, from the comprehensive management of drug-therapeutic monitoring quality and a perspective of risk by the use a drug. Objective: to analyze antecedents in perspective to the integrated management supply of antiretroviral drug system s in order to contribute to improving the quality of life for patients. Materials and Methods: a retrospective qualitative study was performed with hermeneutical approach, the methodological process was the review and the analysis of the protocols of the institution under the study, according to the regulations; field diary and nonparticipant observation processes running on the categories of Inspection, Monitoring and Control. Especially, the pharmaceutical care, this statistical analysis was performed using Spearman coefficient. Results: it was found that protocols from integrated management supply of antiretroviral drugs system are comply. Nevertheless, the pharmaceutical care to each of the patients attending the institution is poor. They showed that in the first quarter of 2013, 97.5% of the patients with antiretroviral regimens were not under pharmaceutical the pharmaceutical care service led by a trained professional that implements other permanent, systematic, holistic and pharmaceutical care.